1999
DOI: 10.1161/01.cir.99.16.2105
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Sodium Pump α 1 , α 3 , and β 1 -Isoform Protein Levels and Na + ,K + -ATPase Activity but Unchanged Na + -Ca 2+ Exchanger Protein Levels in Human Heart Failure

Abstract: The enhanced sensitivity of failing human myocardium toward cardiac glycosides may be, at least in part, attributed to a reduced protein expression and activity of the sarcolemmal Na+,K+-ATPase without a change in Na+-Ca2+ exchanger protein expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
112
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(122 citation statements)
references
References 37 publications
8
112
1
1
Order By: Relevance
“…For example, NCX1 protein expression has been reported to decrease (71), increase (22,61,68), or remain unchanged (22,57) in HF. Although it is generally thought that SERCA2 mRNA levels decrease in CHF (3,11,29,55,61,68), no consensus exists in regard to protein levels, with some studies finding no change (29, 38 -40, 55, 56) and others a decrease (11,21,34,61,68) in expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NCX1 protein expression has been reported to decrease (71), increase (22,61,68), or remain unchanged (22,57) in HF. Although it is generally thought that SERCA2 mRNA levels decrease in CHF (3,11,29,55,61,68), no consensus exists in regard to protein levels, with some studies finding no change (29, 38 -40, 55, 56) and others a decrease (11,21,34,61,68) in expression.…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat surprising, considering that several biochemical studies revealed decreased expression and/or isoform shifts of the Na/K pump in failing or hypertrophied hearts. [13][14][15][16][17] However, most of these studies were performed in tissue homogenates and might reflect changes in nonmyocytes. Moreover, such measurements cannot differentiate between the internalized versus the sarcolemmal Na/K pumps 26 nor between functional and inactive pumps.…”
Section: [Na ؉ ] I Dependence Of the Na/k Pump Is Unchanged In Hf Myomentioning
confidence: 99%
“…12 Higher [Na ϩ ] i could be explained by lower Na/K pump activity, consistent with reports of decreased Na/K pump expression and isoform shifts in some HF models. [13][14][15][16][17] However, functional studies in HF ventricular myocytes are sparse and contradictory. 8,15 Enhanced Na ϩ influx could also raise [Na ϩ ] i , and this explains the higher [Na ϩ ] i in rat versus rabbit ventricular myocytes.…”
mentioning
confidence: 99%
“…This property of the α3β2 isozyme may help in removing Na + ions efficiently from the cytoplasm in the intercalated disc, and as a result H + ions may turn out to be efficiently effluxed. The α3 isoform of the Na + ,K + -ATPase was reported to diminish in left ventricle of failing human myocardium [35]. Therefore, the diminished expression of the α3 isoform in the intercalated disc might account for the decline in the conduction velocity and the consequent arrhythmia in heart failure [36].…”
Section: Functions Of Na + K + -Atpase Isozymesmentioning
confidence: 99%